Dampak Pendekatan Pembelajaran Case Method dan Yang Tidak Menggunakan Case Method Terhadap Hasil Belajar Bulutangkis Pada Mahasiswa Pendidikan Jasmani - Ahmad Arifin; Gumilar Mulya; Nanang Kusnadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze the effectiveness of the Case Method compared with conventional instruction in improving badminton learning outcomes among Physical Education students. Employing an Ex Post Facto design, the research involved two classes selected through cluster random sampling, each consisting of 30 students. Learning outcomes were assessed across cognitive, psychomotor, and tactical domains using written tests, technical performance assessments, and game-play observations with standardized instruments. Data were analyzed using an independent t-test after meeting the assumptions of normality and homogeneity. The results indicate that students taught using the Case Method achieved significantly higher scores than those receiving conventional instruction (t = 13.942; p < 0.001). These findings confirm that the Case Method is more effective in enhancing technical proficiency, tactical understanding, and decision-making skills. Therefore, the Case Method is recommended for integration into badminton instruction to comprehensively improve students’ learning outcomes. Keywords: Case Method, Badminton Learning, Learning Outcomes, Physical Education